PERAN DINAS PENDIDIKAN KOTA PEKANBARU DALAM MENANGGULANGI ANAK PUTUS SEKOLAH PADA TINGKAT PENDIDIKAN SEKOLAH DASAR TAHUN 2012-2015 - Ricardo Saputra; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
A high rate of school dropouts and students who do not continue their education, especially at primary school level, reflects the still limited access to education that could reach the community. Pekanbaru City Department of Education as part of the governance system Pekanbaru implementing the policy and technical education has the responsibility and authority to improve the quality of education in the city of Pekanbaru. The purpose of this study was to determine the role of Pekanbaru City Department of Education in addressing the dropout at the level of primary school education from 2012 to 2015 year. Data analysis method used in this research was qualitative descriptive analysis which seeks explained by phenomena that exist and explore all the facts relating to the issues discussed based on the results of research: the role of Education Department of Pekanbaru in addressing the dropout at the level of school education basic Year 2012-2015.The study states the role of Pekanbaru City Department of Education in addressing dropouts at primary school education level Years 2012-2015 not optimally performing well for the Impact Indicators (Impacts) is still weak supervision of Pekanbaru City Department of Education regarding the management of BOS funds so that there are indications BOS funds misuse. If the government really wants to liberate Indonesia from the child's education cost of education / school, then in case the Government to subsidize the education BOS with a larger amount, so there is no school that levy levy funds from students / parents.Keywords: Role of Education Office of Pekanbaru, Dropouts, Elementary School, Pekanbaru.